External Communication of Autonomous Crews Under Simulation of Interplanetary Missions - Supolkina, Natalia; Yusupova, Anna; Shved, Dmitry; Gushin, Vadim; Savinkina, Alexandra; Lebedeva, Svetlana A.; Chekalina, Angelina; Kuznetsova, Polina (Frontiers in Physiology, 2021)
Two experiments, with 17-day and 120-day isolation, were carried out within the frame of SIRIUS international project at the Institute of Biomedical Problems (Moscow, Russia). Manifestations of the “detachment” phenomenon in crew – MCC communication previously identified in the Mars-500 project were confirmed in this study. As in the Mars-500 experiment, in SIRIUS-19 the landing simulation in the halfway of isolation caused temporary increase of crew communication with MCC. We also revealed a number of differences in communication styles of male and female crewmembers. By the end of the experiment, there was a convergence of communication styles of all SIRIUS crewmembers, and also an increase in crew cohesion.